PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS 1 SD - Agustini, Sri Ayu; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' low understanding of counting materials on subtraction and addition. This research aims to develop smart box learning media to determine the practicality and effectiveness of smart box media to improve student learning outcomes. This research uses the R&D method using the ADDIE model, namely: Analysis, Design, Development, Implementation, Evaluation. The subjects in the research are 3 validators (media experts, languages, materials) teachers and students. Data collection techniques use observation, interviews, questionnaires, tests and documentation. Data analysis uses qualitative data generated from interviews and the results of expert validation questionnaires, teacher and student responses. The results of the smart box media research that have been declared very valid by experts with an overall score of 94% of the category are very valid and the results of use or practicality of 96.8% of the category are very practical and the effectiveness is obtained by 0.85% of the category is very effective. The smart box media developed is valid, practical and effective to improve student learning outcomes in mathematics subjects.